A comment on "Does mathematical coupling matter to the acute to chronic workload ratio? A case study from elite sport" - Lolli, L.; Batterham, A. M.; MacMillan, G.; Gregson, W.; Atkinson, G. (International Journal of Sports Physiology and Performance, 2020)
In a recent article in this journal (the International Journal of Sports Physiology and Performance), Coyne et al compared 2 different calculations of the acute-to-chronic workload ratio (ACWR) using a sample size of 17 basketball players and 28 weight lifters. The 2 different calculations were as follows: